Indexing a Gender Identity in Fictive Dialogue: Bucholtz and Hall’s Identity Principles in Translation - Harrington Fernández, Owen (Hikma, 2018)
The framework for the analysis of identity construction proposed by Bucholtz and Hall (2005) has proved a useful heuristic tool for the study of identity formation in interaction. The aim of this article is to tentatively apply the model to fictive dialogue in translation and test its validity in two ways, firstly, as a framework for the descriptive analysis of identity formation in translation, and secondly, as a tool that can aid the translation of fictive dialogue. The case study is Janice Angstrom, wife of the eponymous Harry Angstrom, in Updike’s «Rabbit» books. Using Bucholtz and Hall’s model, the descriptive analysis will compare the source and target texts for discursive mismatches that distort the intersubjective construction of her identity in interaction. The metapragmatic information yielded by the application of the model will then inform the proposed alternatives, guided by the principles of the model.